Helmet Charger Based Solar Power: A Review of Business Prospect - Syifaul Fuada (Institute of Advanced Engineering and Science, 2016)
Solar power based helmet charger is a product developed by the author and his team that was funded twice by the Ministry of Research and Technology of Higher Education in 2013 and 2014 for ‘Karsa Cipta’ (creative plan) program and ‘Kewirausahaan’ (enterpreneurship) program, respectively. This product has participated in several scientific agendas such as conferences or contests from 2013 to 2015, and is processing the proposal for patent with several claims distinguishing it from other similar innovations. This paper is contained with invention profile and achievement of qualification fulfillment of a superior innovation as well as several considerations of technopreneurship based opportunities or business prospects as a follow up research and development.